An asymptomatic mediastinal cyst in a young child: Case report and summary of the literature. Issue 11 (26th June 2020) - Votto, Martina; Castagnoli, Riccardo; Prevedoni Gorone, Maria Sole; Marseglia, Gian Luigi; Licari, Amelia
Abstract: Bronchogenic cyst is a rare congenital chest malformation that mainly presents with wheeze and feeding issues in early life. A multidisciplinary approach and follow‐up are pivotal for the improvement of lung function, mostly in cases of mediastinal complications. Abstract : Bronchogenic cyst is a rare congenital chest malformation that mainly presents with wheeze and feeding issues in early life. A multidisciplinary approach and follow‐up are pivotal for the improvement of lung function, mostly in cases of mediastinal complications.